Cost-System Functionality, Perceived Usefulness of Cost Information and Performance of Oil Palm Enterprises in Malaysia - Teruki, Neilson (2007)
Changes in the competitive landscape have made reporting of timely and accurate cost information very critical for organizations to sustain and improve their performance. This is particularly relevant for companies competing based on cost effkiency and the oil palm industry is one such industry. Since external market forces determine the price of palm oil, oil palm enterprises have to continuously lower their production costs to sustain and increase profitability. Greater cost management leads to greater efficiency which subsequently leads to better performance. This study investigates the effects of cost-system hnctionality on the performance of oil palm enterprises in Malaysia. The moderating effect of manager's perception of the usefulness of costing information is investigated, since the effectiveness of cost information is also dependent on the perceived usefulness of cost data. A structured questionnaire was used to gather data from oil palm business enterprises located in Sarawak. Data collection was confined to Sarawak in order to avoid the confounding effects of soil and climatic conditions on the performance of oil palm enterprises. The results of this study generally indicate that managers of oil palm enterprises value the cost information provided by highly functional cost system. All the three dimensions of cost functionality are found to be positively associated with the performance of the oil palm enterprises. These findings support the premise that high functional cost systems supply managers with more relevant data, which are used to make performance-enhancing decisions. The positive relationship between cost functionality and performance suggests that is appropriate for the oil palm industry because it is performance-enhancing. The rigid requirements to comply routine estate operating and reporting procedures may have contributed to the insignificant moderating effect of a manager's perceived usefulness on the costfunctionality - performance relationship. The results of this study suggest that when activities are highly routine and operational in nature, high cost system functionality could aid performance, irrespective of the perceived usefulness of cost information. Perceived usefulness of cost information may influence organizational performance in, perhaps, a less structured environment.